Analisis Faktor-Faktor Yang Mempengaruhi Cadangan Devisa di Indonesia Periode 2014–2024 - Prihantini, Nabila; Budi Sekarningsih, Riswanti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the impact of exchange rate, interest rate, inflation, exports, and crisis (COVID-19) on Indonesia’s foreign exchange reserves during the 2014–2024 period. Monthly time series data were used, and both multiple linear regression and logarithmic regression models were employed to identify the relationship between key macroeconomic variables and foreign exchange reserves. The estimation results show that, simultaneously, all independent variables significantly affect foreign exchange reserves. Partially, the exchange rate, interest rate, and inflation exert a negative influence, while exports have a significant positive impact. Interestingly, the COVID-19 crisis variable shows a positive effect, possibly related to fiscal and monetary responses and international assistance received during the pandemic. These findings offer important implications for policymakers and monetary authorities in formulating strategies to maintain the resilience of foreign exchange reserves, especially in facing global economic uncertainty and future crises.